La voce della Grande guerra - Desideri, Paola (Linguistica (Ljubljana), 2018)
From September 1915 until the end of the First World War, the Viennese Romance scholar Leo Spitzer was dispatched to the Censorship section of the Austrian Central Bureau of Information on Prisoners-of-War, where he was in charge of examining the correspondence of the Italian prisoners. In the unusual dual role of censor and philologist, he was the first to collect extensive documentation of popular Italian written texts during a crucial period of Italian linguistic history. The first part of the present paper focuses on the linguistic and communicative properties of the letters included and analyzed in the volume Italienische Kriegsgefangenenbriefe, published by Spitzer in 1921 and trans-lated into Italian in 1976 (Lettere di prigionieri di guerra italiani), whereas the second part deals with stylistic and onomasiological aspects of the circumlocutions expressing hunger, on the basis of Spitzer's study Die Umschreibungen des Begriffes ''Hunger'' im Italienischen (1920) and with reference to his work Motiv und Wort (1918).
Keywords: analiza diskurza; avstrijski romanisti; cenzura; italijanščina; pisma ujetnikov; Spitzer, Leo: Italienische Kriegsgefangenenbriefe; svetovna vojna 1914-1918